Synergy in the knowledge base of U.S. innovation systems at national, state, and regional levels: The contributions of high‐tech manufacturing and knowledge‐intensive services. (7th January 2019) - Leydesdorff, Loet; Wagner, Caroline S.; Porto‐Gomez, Igone; Comins, Jordan A.; Phillips, Fred
Abstract : Using information theory, we measure innovation systemness as synergy among size‐classes, ZIP Codes, and technological classes (NACE‐codes) for 8.5 million American companies. The synergy at the national level is decomposed at the level of states, Core‐Based Statistical Areas (CBSA), and Combined Statistical Areas (CSA). We zoom in to the state of California and in more detail to Silicon Valley. Our results do not support the assumption of a national system of innovations in the U.S.A. Innovation systems appear to operate at the level of the states; the CBSA are too small, so that systemness spills across their borders. Decomposition of the sample in terms of high‐tech manufacturing (HTM), medium‐high‐tech manufacturing (MHTM), knowledge‐intensive services (KIS), and high‐tech services (HTKIS) does not change this pattern, but refines it. The East Coast—New Jersey, Boston, and New York—and California are the major players, with Texas a third one in the case of HTKIS. Chicago and industrial centers in the Midwest also contribute synergy. Within California, Los Angeles contributes synergy in the sectors of manufacturing, the San Francisco area in KIS. KIS in Silicon Valley and the Bay Area—a CSA composed of seven CBSA—spill over to other regions and even globally.